Pengaruh Influencer, live streaming dan content marketing terhadap keputusan pembelian di Tiktok Shop - Tamba, Lilis; Marbun, Sondang; Nadapdap, Kristanty (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the influence of influencers, live streaming and content marketing on purchasing decisions at Tiktokshop (case study of management study program students, FE-UMI). This type of research is quantitative. The analysis method used is multiple linear regression analysis. The total number of respondents in this study was 86 respondents. Based on the results of the t hypothesis test, it can be concluded that influencers have a significant effect on purchasing decisions with a t count value of 3.709> t table 1.989 and a significance value of 0.000 <0.05, live streaming has a significant effect on purchasing decisions with a t count value of 2.014> t table 1.989 and a significance value of 0.470 <0.05, content marketing has a significant effect on purchasing decisions with a t count value of 8.361> t table 1.989 and a significance value of 0.000 <0.05. Based on the results of the F hypothesis test, it can be concluded that simultaneously influencers, live streaming and content marketing have a significant effect on purchasing decisions with a calculated F value of 107.787> F table 2.72 and a significance value of F 0.000 <0.05. The adjusted R square value is 0.790/79%, thus the influence of influencers, live streaming and content marketing on purchasing decisions is 79%.